The long-term effects of early track choice - Dustmann, Christian [Verfasser]; Puhani, Patrick A. [Verfasser]; Schoenberg, Uta [Verfasser] (My University, 2014)
"Despite its efficiency in tailoring education to the needs of students, a tracking system has the inherent problem of misallocating students to tracks because of incomplete information at the time of the tracking decision. This paper investigates the effects of attending a more advanced track in middle school on long-term education and labor market outcomes for Germany, a country with a very rigorous tracking system where the risk of misallocating students to tracks is, due to the early age at which tracking takes place, particularly high. Our research design exploits quasi-random shifts between tracks induced by date of birth, and identifies the long-term effects of early track attendance for a group of marginal students most at risk of misallocation. Remarkably, we find no evidence that for these students, attending a more advanced track leads to more favorable long-term outcomes. We attribute this result to the up- and downgrading of students between tracks after middle school when more information about their potential is available. Overall, our findings underscore that flexibilities built into a tracking system, which allow students to revise initial track choices at a later stage, effectively remedy even a prolonged exposure to a less advanced school environment." (Autorenreferat; BIBB-Doku)

Schüler, die nach der Grundschule nicht nahtlos auf ein Gymnasium wechseln, haben einer Studie des Bonner Instituts zur Zukunft der Arbeit (IZA) zufolge langfristig keine Nachteile bei Beschäftigung, Lohnniveau und Bildungsstand. Die Studie attestiert dem deutschen Schulwesen eine im internationalen Vergleich besonders hohe Durchlässigkeit. Wer als Schüler den Weg zunächst nicht an das Gymnasium findet, hat mit dem Abschluss der Realschule über zweite Wege alle Möglichkeiten bis hin zu einem Studium. Für die Studie wurden Zensus- und Sozialversicherungsdaten der Geburtsjahrgänge 1961 bis 1976 analysiert. (BIBB-Doku)
Keywords: S 1.1 Allgemeinbildende Schule; G 1.3.2 Bildungsverhalten und -verläufe; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; I 2.1 Deutschland; Allgemeinbildendes Schulwesen; Schulwahl; Gymnasium; Schullaufbahn; Bildungsverlauf; Bildungschance; Durchlässigkeit im Bildungssystem; Internationaler Vergleich; Bundesrepublik Deutschland